Państwowa, narodowa, społeczna, partyjna? Nauczanie historii w szkołach publicznych – studium przypadku - Kałużna, Joanna (Przegląd Politologiczny, 2018)
A canon of historical monuments, national holidays, names of streets, the provision of state financing to certain scientific and research centers, supporting initiatives to commemo- rate events and individuals, and building museums are only selected aspects of the historical policy of a state, approached as a detailed policy. This paper concerns another aspect of this policy, namely non-academic state education. A long-term educational reform was launched on September 1, 2009. It provides for the changes to be fully implemented by September 2014. They will concern a number of fields, but there is one that has become the core of a pe- culiar political conflict – the reform in teaching history. The paper presents the conflict, its turning points and, first and foremost, its rhetoric – the character of statements, selection of vocabulary and ways of evoking the right associations employed by both parties to the con- flict. The paper also discusses the assumptions of the reform and indicates the most important legal acts and statements by the Minister of National Education, thereby providing a legal framework for the arguments of the conflicting parties.